Etika Politik Dalam Pemanfaatan Ruang Publik - Umiyati Haris (Jurnal Administrasi Karya Dharma, 2023)
This research aims to analyse political ethics in the utilisation of public space within the framework of a democratic state in Indonesia. The urgency of political ethics in the utilisation of public space is that political ethics plays an important role in ensuring that the utilisation of public space does not violate human rights and principles of social justice. The public space in this research is the mass media. This research is qualitative with descriptive-analytic techniques in describing the research results. Data sources were obtained through literature searches. The data analysis technique uses the Miles and Huberman model. The results show that political ethics is needed in the utilisation of public space on the grounds that political ethics will limit mass media corporations to fully control the media for their personal interests. Mass media controlled by political elites are sometimes used to win elections, for example. Political ethics in the utilisation of public space, especially mass media, is still lacking in Indonesia. Mass media requires the application of political ethics in it because it is related to freedom of expression in the public sphere in a democratic country. Thus, political ethics is needed in the utilisation of public space in freedom of expression, one of which is mass media